2012
DOI: 10.1029/2011gl050444
|View full text |Cite
|
Sign up to set email alerts
|

A chain of magnetic flux ropes in the magnetotail of Mars

Abstract: [1] The interaction of Mars with the solar wind leads to the formation of a magnetotail through which significant quantities of planetary plasma are transported. Of particular interest is the extent to which this plasma transport could be affected by magnetotail dynamics, for example by magnetic reconnection and flux rope formation. Here we show observations from Mars Global Surveyor of multiple flux ropes observed in Mars' magnetotail current sheet. A chain of at least three flux ropes is observed; based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 24 publications
2
41
0
Order By: Relevance
“…At Mars, observations of magnetic reconnection (Dubinin et al, 2008;Eastwood et al, 2008;Harada et al, 2015aHarada et al, , 2017, flux rope formation (DiBraccio et al, 2015;Eastwood et al, 2012;Hara et al, 2017), current sheet flapping , Marsward and tailward ion flows (Harada et al, 2015b), magnetic lobe dependence on IMF orientation Romanelli et al, 2015) and ionosphere magnetization , and bulk plasma escape (e.g., Brain et al, 2010;Halekas et al, 2016) have been reported in the magnetotail. At Mars, observations of magnetic reconnection (Dubinin et al, 2008;Eastwood et al, 2008;Harada et al, 2015aHarada et al, , 2017, flux rope formation (DiBraccio et al, 2015;Eastwood et al, 2012;Hara et al, 2017), current sheet flapping , Marsward and tailward ion flows (Harada et al, 2015b), magnetic lobe dependence on IMF orientation Romanelli et al, 2015) and ionosphere magnetization , and bulk plasma escape (e.g., Brain et al, 2010;Halekas et al, 2016) have been reported in the magnetotail.…”
Section: 1029/2018gl077251mentioning
confidence: 99%
“…At Mars, observations of magnetic reconnection (Dubinin et al, 2008;Eastwood et al, 2008;Harada et al, 2015aHarada et al, , 2017, flux rope formation (DiBraccio et al, 2015;Eastwood et al, 2012;Hara et al, 2017), current sheet flapping , Marsward and tailward ion flows (Harada et al, 2015b), magnetic lobe dependence on IMF orientation Romanelli et al, 2015) and ionosphere magnetization , and bulk plasma escape (e.g., Brain et al, 2010;Halekas et al, 2016) have been reported in the magnetotail. At Mars, observations of magnetic reconnection (Dubinin et al, 2008;Eastwood et al, 2008;Harada et al, 2015aHarada et al, , 2017, flux rope formation (DiBraccio et al, 2015;Eastwood et al, 2012;Hara et al, 2017), current sheet flapping , Marsward and tailward ion flows (Harada et al, 2015b), magnetic lobe dependence on IMF orientation Romanelli et al, 2015) and ionosphere magnetization , and bulk plasma escape (e.g., Brain et al, 2010;Halekas et al, 2016) have been reported in the magnetotail.…”
Section: 1029/2018gl077251mentioning
confidence: 99%
“…Chains of flux ropes have also been observed in the magnetotail current sheet by MGS [Eastwood et al, 2012a]; for example, between 14:45 and 14:55 UT on 14 January 2000, MGS crossed the magnetotail current sheet and observed a series of three flux rope signatures. Each flux rope was moving tailward, and a very good fit to a force-free flux rope model was obtained for the first and second structures.…”
Section: Reconnection In the Magnetotail Current Sheetmentioning
confidence: 92%
“…Once formed by this secondary instability, the islands are periodically ejected in the reconnection outflow (see Figure 16.1c). Such periodic ejection could also create a chain of islands; this has been suggested to explain observations of flux rope chains in the magnetotails of Mars and Earth where the system size was not found to be commensurate with the chain size and duration [Eastwood et al, 2012a;Hietala et al, 2013]. Again Figure 16.1 shows antiparallel reconnection, and so the secondary island consists of closed loops.…”
Section: Quasi-two-dimensional Structurementioning
confidence: 94%
“…Flux ropes signatures have also been observed beyond the terminator within the induced magnetotail of Mars (Eastwood et al, 2008(Eastwood et al, , 2012 and Venus (Slavin et al, 2009;Zhang et al, 2012a). The flux ropes of the magnetotail of Mars and Venus are found to take place in-between crossings of the central current sheet that separate oppositely orientated magnetic field of the magnetotail, and have been related to magnetic reconnection (Eastwood et al, 2008;Zhang et al, 2012a).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%
“…The flux ropes of the magnetotail of Mars and Venus are found to take place in-between crossings of the central current sheet that separate oppositely orientated magnetic field of the magnetotail, and have been related to magnetic reconnection (Eastwood et al, 2008;Zhang et al, 2012a). Flux ropes of the Mars magnetotail are characterised by similar weak magnetic field strength and radial size as filamentary ionospheric flux ropes (Eastwood et al, 2008(Eastwood et al, , 2012, whereas flux ropes from the Venus magnetotail have been observed with larger sizes (1000's km) (Slavin et al, 2009;Zhang et al, 2012a).…”
Section: Contents Lists Available At Sciencedirectmentioning
confidence: 99%